2020
DOI: 10.3389/fpsyt.2020.00470
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of the Cut-off Score for Nine-Item Internet Gaming Disorder Scale–Short Form (IGDS9-SF) in a Chinese Context

Abstract: Background: The nine-item Internet Gaming Disorder Scale-Short-Form (IGDS9-SF) is a self-reported screening measure based on the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) criteria. It has been used to assesses symptoms and prevalence of Internet Gaming Disorder (IGD) in general population. Despite its widespread use, there is confusion arising from the recommended cutoff score for a positive diagnosis. This study aimed to identify the appropriate cutoff score for IGDS9-SF in a Chinese conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 18 publications
2
47
0
Order By: Relevance
“…This can substantially reduce the time for clinicians to diagnose and assess IGD symptoms. To this end, clinical studies have suggested adopting a cutoff of 32 points when diagnosing between disordered and nondisordered gamers [ 67 ]. Moreover, due to the robust psychometric properties reported across 15 language versions, the IGDS9-SF can also be used in worldwide epidemiological studies examining IGD [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can substantially reduce the time for clinicians to diagnose and assess IGD symptoms. To this end, clinical studies have suggested adopting a cutoff of 32 points when diagnosing between disordered and nondisordered gamers [ 67 ]. Moreover, due to the robust psychometric properties reported across 15 language versions, the IGDS9-SF can also be used in worldwide epidemiological studies examining IGD [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PGSI is a 9-item, well-validated measure of problematic gambling, with response options of “never” (scored 0), “sometimes” (scored 1), “often” (scored 2), and “almost always” (scored 3), giving a total score between 0 and 27, with scores of 3–7 indicating moderate-risk gambling and 8 or over indicating problem gambler status [ 28 ]. The IGD is a 9-item, well-validated measure of problematic gaming, scored on a 5-point Likert-scale, with a possible range from 9 to 45, with higher scores indicating more severe problems, and a score of 32 or above used to indicate “disordered gaming” [ 30 ]. Table 1 summarises sample demographic characteristics, PGSI and IGD scores, and loot box expenditure.…”
Section: Methodsmentioning
confidence: 99%
“…The total score can range between 9 and 45. A recent study identified a cut-off value of 21, in order to distinguish disordered and non-disordered gamers [18]. The scale was validated in the Italian language by Monacis et al [19].…”
Section: Instrumentsmentioning
confidence: 99%